The role of environmental responsibility in mediating value-driven low-carbon consumption intentions: evidence from Shanxi province, China - Hongxia Jing; Ratneswary Rasiah (Sustainable Futures, 2025)
Low-carbon consumption is essential for alleviating climate change caused by human activities, and environmental values, as a significant determinant of consumer behavior, are pivotal in shaping the propensity to engage in low-carbon consumption. This study, grounded in the Value-Belief-Norm (VBN) theory, examines how environmental values influence low-carbon consumption intention among residents in Shanxi Province, a major energy-producing region in China, with a focus on the mediating role of environmental responsibility. A theoretical framework integrating environmental values, environmental responsibility, and low-carbon consumption intention was empirically tested using survey data from 528 valid respondents. Findings reveal that biosphere values and altruistic values significantly and positively influence low-carbon consumption intention, whereas the impact of egoistic values is not significant. Additionally, environmental values significantly and positively predict environmental responsibility, which in turn significantly contributes to low-carbon consumption intention. Environmental responsibility fully mediates the relationship between altruistic values and low-carbon consumption intentions, while partially mediating the relationship between biosphere values and low-carbon consumption intentions. The study's findings enhance the theory of value-driven sustainable consumption behavior and offer empirical evidence for government agencies to develop tailored carbon emission reduction policies and for businesses to implement targeted low-carbon marketing, serving as a significant reference for advancing the Sustainable Development Goals (SDGs).